Dexmedetomidine for Chemical Restraint of a Brazilian Tapir (Tapirus terrestris) - Vieira Nunes, Marllos Henrique; Eduardo Cavalcante das Neves; Elaine Christina Oliveira do Carmo; Danielle Saldanha de Souza Araújo; Cassio Toledo Messias; Juliana Tessália Wagatsuma (Acta Scientiae Veterinariae, 2022)
Background: The Brazilian tapir (Tapirus terrestris), considered the largest land mammal in South America, is a vulnerable species in terms of its degree of conservation. In captivity, its health is evaluated through behavioral and physical observation and laboratory exams, and in some cases, chemical restraint, to reduce stress. Dissociative anesthetics and sedatives are used for the sedation of these animals, and few studies have reported the use of dexmedetomidine and its effects when associated with other drugs in chemical containment protocols; therefore, this work reports its use, in conjunction with ketamine and midazolam, in a young Brazilian tapir. Case: A male Brazilian tapir, male, weighing 89 kg, 1 and a half year old, housed at CETAS in Rio Branco, Acre, was chemically restrained with dexmedetomidine (7 µg/kg), ketamine (1.5 mg/kg), and midazolam (0.2 mg/kg) for venous blood collection, oral and rectal mucosal swabs, and microchipping. The protocol was administered intramuscularly to the right triceps brachii, after physical restraint. After 5 min of application, the animal assumed sternal recumbency and presented reflux. After 15 min, the patient was placed in the right lateral decubitus position. During collection, heart rate (48 ± 10 bpm), respiratory frequency (29 ± 1 mpm), rectal temperature (38.1 ± 0.18 °C), oxyhemoglobin saturation (97 ± 1%), and electrocardiographic tracing were recorded. The tapir showed deep sedation, immobility, good muscle relaxation, discreet medial palpebral reflex, and bilateral rotation of the eyeball. After 40 min of protocol administration, sedative reversal was performed intramuscularly with 14 µg/kg atipamezole. Five min after administration, the tapir showed signs of mild sedation. After 10 min, he assumed the quadrupedal position, remained in this position for 8 min, and gently resumed the sternal decubitus. After only 20 min, he resumed the quadrupedal position, with mild ataxia and good muscular and conscious tone. After 50 min, the patient was discharged from anesthesia. Discussion: Domestic horses are phylogenetically close to tapirs, so the choice of drugs and doses of the protocol used was based on their use in horses, and on studies carried out with tapirs as well. Despite being docile and passive, the tapir was not conditioned and did not allow the manipulation and collection of samples collaboratively; therefore, it was chemically contained. The physical restraint performed did not generate satisfactory immobilization of the tapir, resulting in agitation and stress and causing the needle to break. The reflux presented by the tapir minutes after sedation and at recovery was induced by dexmedetomidine, and only the undigested banana pieces were offered to the animal. Reflux plus stress from extensive fasting and suboptimal physical restraint was responsible for the change in the tapir's eating behavior, with possible stress gastritis 24 h after chemical restraint. Only one study reported the use of dexmedetomidine in tapirs, associated with continuous infusions of ketamine, midazolam and guaiacol glyceryl ether for moderate to long-term field procedures. Sedative reversal of dexmedetomidine by atipamezole reduced the recovery time and the risk of death from cardiorespiratory depression. The anesthetic combination used was effective, promoting immobility, muscle relaxation, and stability of the physical parameters evaluated, with rapid and gentle induction and an adequate level of sedation for the objective, good sedative reversal, and anesthetic recovery. Keywords: anesthesia, anesthetic management, wild animals, mammals, sedative.